Intestinal Polyposis Syndromes - Silva, Ana Daniela de Oliveira e (2017)
Introduction: Currently, colorectal carcinoma is the most prevalent gastrointestinal cancer in the world and the second cause of death from malignant disease. Hereditary polyposis syndromes account for about 1% of colorectal cancer. Familial Adenomatous Polyposis is the second most common inherited colorectal cancer syndrome and it is characterised by the early development of tens to thousands of adenomatous polyps and/or cancer in the colon and rectum. MUTYH-Associated Polyposis is associated with dozens or few hundreds of adenomatous polyps in the colon and an increased risk of colorectal cancer. Objective: The present work will focus on adenomatous polyposis syndromes, in particular on the description of two families with rare presentations and review of the literature. Clinical Cases: The first clinical case is a 17-year-old male who presented with a phenotype characterised by non-progressive bowing of the right leg detected at 18 months of age caused by a fibula malformation (pachydysostosis) and a large exophytic osteoma of the left radius, noticed at the age of 15 years, without gastrointestinal symptoms. Detailed clinical and radiological characterisation revealed multiple osteomas (of the left fibula, left ilium, metacarpals and mandible), skin lesions and dental abnormalities, raising the hypothesis of Gardner Syndrome. This diagnosis was confirmed by genetic testing (a de novo mutation in the APC gene was identified) and endoscopic investigation, which identified the presence of multiple adenomatous polyps throughout the colon, ileum and stomach. The second clinical case is the report of a 34-year-old male with adenomatous colonic polyps (45 polyps at the age of 33 years) and a family history of adenomatous polyposis and colon neoplasia. The patient's family history suggested an autosomal dominant inheritance pattern, which would be in favour of a mutation in APC gene (autosomal dominant inheritance) rather than mutations in MUTYH gene (autosomal recessive pattern), which ended up being the correct diagnosis. Final Remarks: The clinical cases here described illustrate the diversity of presentations in patients with adenomatous polyposis syndromes and the challenges in their accurate recognition and diagnosis. The first case points out the difficulties in establishing an early diagnosis in a de novo APC mutation, which is essential for an appropriate management. It also emphasizes the importance of a detailed clinical characterization, including FAP extra-colonic manifestations, and the need of a multidisciplinary team in reference centres, articulated with international experts. The second clinical case highlights the importance of a detailed family history and of international guidelines, in particular for the appropriate genetic testing strategy.